Cidadania e desenvolvimento local: o Conselho Municipal de Saúde de Palmas-TO sob a perspectiva da gestão social - Nunes, Carine de Oliveira (Universidade Federal do Tocantins, 2018)
This dissertation proposed to analyze the municipal health council of Palmas-TO under the perspective of Social Management. Specifically: i) to discuss how the public policy management councils were institutionalized in Brazil. ii) describe the organization and operation of the municipal health council of Palmas -TO. iii) to identify the characteristics of the Social Management present in the municipal health council of Palmas-TO, based on the criteria of the Deliberative Citizenship analysis. In the theoretical foundation were used studies on social management, deliberative citizenship and its categories. The data collection was qualitative in nature through documentary research, questionnaire, interviews and focus group. The interviews were carried out with 8 counselors covering Government, Users and Health Workers. The interpretation was based on the categories and criteria of evaluation of deliberative citizenship developed by Tenório et al. (2008). The results indicate that there is partial compliance with the deliberative citizenship criteria and the health council's potential for the endogenous implementation of Social Management.